(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2017)
Sarcomas are malignant neoplasms originating from mesodermal tissues that constitute connective tissues of the body. This seven years old girl was born after an uncomplicated full term pregnancy. Her physical status at birth was unremarkable. Her younger sister is healthy. At age of one and a half year she developed swelling over posterior head and neck region that was gradually increasing. The rate of growth was more rapid from October 2014. She was admitted in National Institute of Neurosciences & Hospital (NINS). Local examination showed a giant swelling 22X17X21 cm in size over posterior head and neck region, fixed to the sub-occipital bone, firm in consistency. Her general and neurological examination revealed no abnormalities.The authors present a case of a giant soft tissue fibrosarcoma of posterior head and neck of a seven years old girl. The case has been discussed. Journal of National Institute of Neurosciences Bangladesh 2015;1(2): 65-68